ASSESSMENT OF WIND PRESSURE BY EUROCODE-1, TS 498 AND CFD ANALYSES FOR DOUBLE-SLOPED ROOF BUILDING - Zeyrek, Halil; Bekiroglu, Serkan (YILDIZ TECHNICAL UNIV, 2019)
In this study, building external wall pressures induced by wind velocity for rectangular planned-buildings with several roof slopes are determined using two wind standards such as Eurocode-1 and TS 498 and two-dimensional computational fluid dynamics (CFD) analysis. In CFD analyses, wind velocity function produced according to Eurocode-1 is used as velocity input. At the end of the study, wall pressures obtained by using Eurocode-1, TS 498 and CFD analyses are compared on the same peripheral region of the buildings. It is concluded that the results of TS 498 are not at a sufficient level according to the results of Eurocode-1 and CFD analyses. The results of Eurocode-1 and CFD analyses match with each other regarding positive and negative pressures on the same peripheral region. Eurocode-1 propounds higher values than those of CFD except values obtained on regions at the folded-corners of some buildings.
Keywords: Computational fluid dynamics (CFD) analyses; Eurocode-1 (TS EN 1991-1-4); TS 498; rectangular planned to build with double-sloped roof; external wall pressure; wind velocity function; Engineering